Clinical Characteristics and Hospitalisation Outcomes of Hypoglycaemia in Hospitalised Patients With Type 2 Diabetes Mellitus - Krishnamoorthy, Swarna; Pandurangan, Viswanathan; Varadan, Sivaprakash; Gopalan, Sowmya; R B, Sudagar Singh (Scripta Medica, 2024)
Background/Aim: Strict glycaemic control delays the onset as well the progression of diabetes related microvascular complications. The major roadblock in achieving the target glycated haemoglobin (HbA1c) and blood glucose levels is hypoglycaemia. The aim of this study was to assess the clinical characteristics and outcomes of hypoglycaemia in the type 2 diabetes mellitus (T2DM) hospitalised patients.Methods: This was an observational study done for nine months in T2DM patients who had documented hypoglycaemia (blood glucose < 70 mg/dL) during the hospital stay. T2DM patients with hypoglycaemia on admission, hypoglycaemia due to anti-diabetic drug overdose, intensive care unit (ICU) patients with hypoglycaemia were excluded from the study. Eligible patients were categorised into two groups as symptomatic and asymptomatic hypoglycaemia. Clinical features, risk factors, hospitalisation outcome were compared between the symptomatic and asymptomatic hypoglycaemia group.Results: Two hundred patients were enrolled in this study (n = 89, symptomatic group and n = 111, asymptomatic hypoglycaemia). Hypoglycaemic episode in past was significantly associated with symptomatic hypoglycaemic events during hospitalisation [34 (38.2 %) vs 27(24.3 %)], p = 0.01. Admission blood glucose levels (mg/dL), HbA1c (%) were significantly higher in symptomatic hypoglycaemia group [(225.93 vs 178.72, p = 0.008), (8.55 ± 2.49 vs 7.72 ± 1.82, p = 0.007)], respectively. The blood glucose level during the hypoglycaemia episode was significantly higher in patients with asymptomatic hypoglycaemia group (56.38 ± 9.51 vs 44.22 ± 11.21 mg/dL, p < 0.001). Patients with HbA1c ≤ 6 % were significantly higher in asymptomatic hypoglycaemia (n = 12, 10.8 % vs n = 2, 2.24 %, p = 0.02). Majority recovered fully without complications and got discharged (n = 155, 77.5 %).Conclusion: In presented study, symptomatic hypoglycaemic patients had significantly higher admission blood glucose levels and HbA1c %. Patients with HbA1c < 6 % were significantly higher in asymptomatic group. Past history of hypoglycaemia was significantly associated with symptomatic hypoglycaemia during hospitalisation.